Topical application of the HSP90 inhibitor 17-AAG reduces skin inflammation and partially restores microbial balance: implications for atopic dermatitis therapy - Krzysztof Sitko; Ewa Piotrowska; Magdalena Podlacha; Natalia Zagórska; Michał D. Starke; Magdalena Trzeciak; Stefan Tukaj (Scientific Reports)
Abstract Heat shock proteins belonging to the HSP90 family promote inflammation and are potential therapeutic targets in inflammatory and autoimmune diseases. Here the effects of the HSP90 inhibitor 17-AAG applied topically were evaluated in a DNCB-induced murine model of atopic dermatitis (AD). The use of 17-AAG improved clinical disease activity without causing toxicity in the animals. Topical application of 17-AAG resulted in reduced epidermal hyperplasia, decreased expression of TSLP, IL-5, and IL-6, as well as reduced activation of NF-κB in the skin. In addition, the eosinophil proportion in the blood and eosinophil peroxidase (EPX) activity in the skin were significantly reduced in 17-AAG-treated AD mice. The inhibitory effects of 17-AAG on the production of epidermal alarmins, T-helper cell-associated cytokines, and ROS release were demonstrated in cultures of activated human keratinocytes, CD4+ T lymphocytes, and eosinophils, respectively. Finally, next-generation sequencing metagenomic approaches revealed that topical application of 17-AAG partially restored the normal gut microbiome in AD mice. Moreover, 17-AAG inhibited Staphylococcus aureus biofilm formation in vitro. The findings of this study, combined with the observed increase in HSP90 and EPX activity in the leukocytes of the analyzed cohort of AD patients, support the potential therapeutic use of HSP90 inhibitors in individuals with AD.